ТАЛАБАЛАРГА ТАСВИРИЙ САНЪАТ МАШҒУЛОТЛАРИНИ ТАШКИЛ ЭТИШНИНГ ИЛМИЙ МЕТОДИК АСОСЛАРИ - Алдабергенов, А.У. (SCIENCE and SOCIETY, 2022)
The article is devoted to one of the topical issues of training the future art teacher, the role of scientific knowledge and practical skills in pedagogical drawing. Practical advice is presented about the implementation of educational productions.